Spatial Regression of reproduction of dengue fever mosquito's transmitter phenomenon in the university municipality-Jeddah province – Kingdom of Saudi Ariba -2018: pSpatial Regression of reproduction of dengue fever mosquito's transmitter phenomenon in the university municipality-Jeddah province – Kingdom of Saudi Ariba -2018 - Elhafian, Mubarak (International Journal of Scientific Research and Management (IJSRM), 2020)
The method of Geographical Information System is used for building statistical models to estimate the number s of mosquitoes which are effected by natural factors. Decisions makers and mosquitoes' combater; in particular, those carriers to Dengue Fever, regarding to set plans and methods to fight them depending on the weighted least square model.The study aimed to build a model known by regressions spatial to the phenomenon of mosquitoes' reproduction within the neighborhood of the Jeddah Municipal. Also, studying the quality of spatial models which is estimated; including studying and determining reasons that lead to mosquitoes' reproduction carry Dengue Fever within Jeddah City. The researcher also did not forget the possibility of calculating or estimating the numbers of mosquitoes carry Dengue Fever in any single spot within the neighborhood whereas two factors were determined which are the temperature and humidity to estimate numbers of mosquitoes carry Dengue Fever. Data were collected to average of the numbers multiplied mosquitoes carry Dengue Fever in Jeddah City in weeks from (1-45) year 2018 including the average of temperature and humidity for the same period; whereas the determined Coefficient was R2 = 55% and  the result of that model showed fifty five percent of the total changes happen in mosquitoes reproduction within the municipal of Jeddah K.S.A. AIC method was used to select the best model. Whereas the residuals in the model showed to un-annotator model and they were determined that return to the other environmental affect which are considered to be the foci to mosquitoes reproduction because of the way of water overstocking, sanitation, swamp of wasted water and residents' customs and traditions; whereas the targeted study area has various numbers of foreigners from different parts of the world which made a differences and variety in customs and traditions.